Bifurcation Diagram of W(u_j;τ)-Function with (p,q)-Parameters - Madhi, Zainab S.; Abdul Hussain, Mudhir A. (Iraqi Journal of Science, 2022)
This study aims to classify the critical points of functions with 4 variables and 8 parameters, we found the caustic for the certain function with the spreading of the critical points. Finally, as an application, we found the bifurcation solutions for the equation of sixth order with boundary conditions using the Lyapunov-Schmidt method in the variational case.